Post-competition blood lactate concentration in regional level and masters athletes - Ditroilo, M.; Castagna, C.; Lucertini, F. (New Studies in Athletics, 2012)
The measurement of blood lactate concentration ([La]b) following competition or maximal and submaximal exercise have been widely used to assess exercise intensity, to predict performance and to quantify the contribution of the anaerobic metabolism to the effort However, few studies have focused on athletics and those available have been conducted with elite athletes. Accordingly, the aim of the present descriptive study is to assess post-competition [La]b in 72 young regional level and 36 Masters age group athletes. Overall, mean values (standard deviation) of [La]b were 8.13 (1.08), 12.46 (0.86), 15.12(1.70), 12.73 (1.69), 15.00 (1.10) mM in males and 8.64 (0.21), 12.89 (2.16), 14.97 (2.26), 14.58 (0.50), 14.22 (0.74) mM in females for the 60m, 200m, 400m, 800m and 1500m distances respectively. Male Masters athletes, aged between 36 and 71 years, reached [La]b values between 6.57 and 18.08 mM, 7.75 and 18.53 mM, 8.25 and 17.00 mM in the 200m, 400m, 800m distances respectively, depending on age and performance. The results obtained have the potential to provide a better insight into the anaerobic metabolism of regional level and Masters athletes, with implications for training programmes.